2020
DOI: 10.1016/j.childyouth.2020.104849
|View full text |Cite
|
Sign up to set email alerts
|

Untangling child welfare inequalities and the ‘Inverse Intervention Law’ in England

Abstract: This article addresses some potential limitations of key findings from recent research into inequalities in children's social services by providing additional evidence from multilevel models that suggest the socioeconomic social gradient and 'Inverse Intervention Law' in children's services interventions are statistically significant after controlling for possible confounding spatial and population effects. Multilevel negative binomial regression models are presented using English child welfare data to predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 46 publications
1
28
1
Order By: Relevance
“…There are no international replications of Eckenrode et al's study to date, however, Webb et al's English study 13 found that greater income inequality in the local administrative region was associated with greater inequalities in child welfare intervention rates between more deprived and less deprived neighbourhoods. However, the sample size of local authorities was only 18, and there was no analysis of the relationship between income inequality and state interventions more generally.…”
Section: Introductionmentioning
confidence: 89%
“…There are no international replications of Eckenrode et al's study to date, however, Webb et al's English study 13 found that greater income inequality in the local administrative region was associated with greater inequalities in child welfare intervention rates between more deprived and less deprived neighbourhoods. However, the sample size of local authorities was only 18, and there was no analysis of the relationship between income inequality and state interventions more generally.…”
Section: Introductionmentioning
confidence: 89%
“…IMD scores were standardised for all analyses. A one-standard deviation increase in IMD score is approximately equal to an increase of 10 per cent of the population with equivalised household incomes that are less than 60 per cent of the median national income (Webb, et al 2020). (Jones, 2014).…”
Section: Estimationmentioning
confidence: 99%
“…For example, what proportion of a national budget goes to preventive services as opposed to statutory services, or to what extent Indigenous people can access resources and power to create independent services. Bywaters et al (2019) and Webb et al, (2020) for example found that the inequalities relating to family deprivation were the largest effect on outcomes, although other institutional level factors did have an effect, while Hood et al (2020) found through qualitative methods that cuts to community services and a more pro-active attitude to child neglect were key drivers of demand from 'external' factors. Understanding how these are produced by the political decisions of the day are key to a complex understanding of how decision outcomes happen.…”
Section: How Critical and Qualitative Approaches Can Help Extend The Dmementioning
confidence: 99%